1973
DOI: 10.1175/1520-0477(1973)054<1220:pmbmua>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Modification By Major Urban Areas

Abstract: Historical weather records at eight American urban areas of varying size, type, and climate were studied for indications of inadvertent precipitation modification. The six largest cities all had experienced warm seasonal rainfall increases of 9 to 17% during the 1955-70 period. The increases in the Midwest cities occurred largely with cold frontal systems, but in the coastal cities they were largely during air mass (non-frontal) conditions. The Midwest increases also were found to occur as enhancement, not ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
110
0
5

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(126 citation statements)
references
References 2 publications
11
110
0
5
Order By: Relevance
“…In general, they have attributed the effect to the urban heat island circulation, even though a possible role of air pollution has been suggested. Several authors have found evidence of urban effects on the local weather phenomena (Myrup, 1969;Braham, 1974;Huff and Changnon, 1973;Semonin and Changnon, 1974;Changnon et al, 1981;Landsberg, 1981;Karl et. al., 1988, Balling andIdso, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In general, they have attributed the effect to the urban heat island circulation, even though a possible role of air pollution has been suggested. Several authors have found evidence of urban effects on the local weather phenomena (Myrup, 1969;Braham, 1974;Huff and Changnon, 1973;Semonin and Changnon, 1974;Changnon et al, 1981;Landsberg, 1981;Karl et. al., 1988, Balling andIdso, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Those changes cause the phenomenon known as "heat island" and associated effects (Jáuregui, 1997(Jáuregui, , 2000(Jáuregui, , 2004. According to Huff and Changnon (1973), the heat island effect has increased convective precipitation. In large urban areas, as in the Federal District, changes in the albedo of the surface may result in a warmer surface, thus a more unstable atmosphere and adequate conditions for intense storms to occur.…”
Section: Introductionmentioning
confidence: 99%
“…Many climatological studies have shown increases in precipitation and aggravation of convective storm activity (Huff and Changnon, 1973;Schickedanz, 1974;Changnon, 1978 and others), though there have been a few investigations that questioned the nature and the magnitude of urban effects on precipitation (e.g., Pittock, 1977). Another urban anomaly which is most noticeable is that a city has a higher temperature than its suburbs; this phenomenon is called a heat island.…”
Section: Introductionmentioning
confidence: 99%